An Alternative Conditional Asymmetry Specification for Stock Returns - Kurt Brännäs; Niklas Nordman (Center for Economic Studies and ifo Institute (CESifo), 2001)
The paper advances the log-generalized gamma distribution as a suitable generator of conditional skewness. Based on the NYSE composite daily returns an asMA-asQGARCH model along with skewness dynamics is estimated. The results indicate a skewness that varies between sizeable negative skewness and almost symmetry. The conditional variance and skewness measures are negatively correlated.
Keywords: 330; Time series; finance; nonlinearity; skewness; gamma; estimation; NYSE